2010 Internet of Things (IOT) 2010
DOI: 10.1109/iot.2010.5678456
|View full text |Cite
|
Sign up to set email alerts
|

Product Empire — Serious play with barcodes

Abstract: Despite the ubiquity of barcodes there exists no common product repository available today linking product master data to the corresponding barcodes. This paper proposes a social network game (Product Empire) that motivates users to scan barcodes and to enter basic product information, such as product name, brand and category and to upload a picture of the product. This user-generated product repository aims at providing a base to link real world objects with virtual information. After a first prototype has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…More similar to our work, we would argue, are approaches such as Wood et al [15]'s Department of Hidden Stories, which linked digital tales to physical books by scanning ISBN barcodes, or Budde and Michahelles [1]'s Product Empire, which gamified scanning of product barcodes (but used the action to build up a product database, rather than to add social interaction). Finally, commercial augmented reality applications such as Layar, 3 Aurasma 4 or Blippar 5 allow any object to be tagged with digital content, but recognition relies on objects being visually alike, and there is no way to visibly tell which objects are marked-up.…”
Section: Introductionsupporting
confidence: 61%
“…More similar to our work, we would argue, are approaches such as Wood et al [15]'s Department of Hidden Stories, which linked digital tales to physical books by scanning ISBN barcodes, or Budde and Michahelles [1]'s Product Empire, which gamified scanning of product barcodes (but used the action to build up a product database, rather than to add social interaction). Finally, commercial augmented reality applications such as Layar, 3 Aurasma 4 or Blippar 5 allow any object to be tagged with digital content, but recognition relies on objects being visually alike, and there is no way to visibly tell which objects are marked-up.…”
Section: Introductionsupporting
confidence: 61%
“…However, French et al [46] argue that the burden of creating and maintaining a complete product bar code database makes this method impractical and unfeasible. However, multiple studies have since then showed that crowdsourcing can be used to build and maintain a product bar code database, particularly when combined with game play incentives [18,33]. Similar to the work by Martin et al [79] and Cullen et al [28], the collected data can be manually coded and analyzed as valid data for nutritional assessment.…”
Section: Text Analysismentioning
confidence: 99%
“…OAuth 2.0 is currently an "Internet Draft": created in an attempt to simplify the original OAuth 1.0 and 1.0a specifications 4 by leveraging standard TLS and SSL encryption to exchange credentials and access tokens between service providers and their clients. In addition to simplifying authentication for developers, OAuth 2.0 includes support for various flows, for web servers, native desktop and mobile apps with a UI, as well as devices where user authentication is not practical or possible such as PVRs set top boxes, home automation equipment, sensors and actuators.…”
Section: Facebookmentioning
confidence: 99%
“…Furthermore, it is not clear that exposing the WoT as just another Facebook application is the best approach. The Product Empire [4] game links things to people by taking a similar approach to FourSquare, Similar to how people "check in" with Foursquare, users enter information about products they scan with barcodes. Over time the system builds up a "crowd sourced" up-to-date product repository.…”
Section: Osns and The Web Of Thingsmentioning
confidence: 99%
See 1 more Smart Citation